Lee's Tigers : The Louisiana Infantry in the Army of Northern Virginia - Jones, Terry L., 1952- (Book collections on Project MUSE., 2002)
Sometimes called the "wharf rats from New Orleans" and the "lowest scrapings of the Mississippi," Lee's Tigers were the approximately twelve thousand Louisiana infantrymen who served in the Confederate Army of Northern Virginia from the time of the campaign at First Manassas to the final days of the war at Appomattox. Terry L. Jones offers a colorful, highly readable account of this notorious group of soldiers renowned not only for their drunkenness and disorderly behavior in camp but for their bravery in battle. It was this infantry that held back the initial Federal onslaught at First Manass.